Graphic and Sculptural Images in the Educational Environment of an Architectural Student: Peculiarities of Visualization of Artistic Language - Irina, Portnova V.; Tatiana, Portnova V. (Journal of Ecohumanism, 2024)
This article dwells on a synthesis of spatial plastic art - communications, performing an informative educational role. The features are revealed and the significance of graphic, plastic and pictorial communications in the educational process of the student-architect and their impact on an architecture were emphasized. The pictorial and expressive capabilities of each species are noted. The drawings are also revealed as a basis of creativity which has various means of expression such as sketches, etudes. A sculpture was considered from the point of view of its plastic qualities and commonality with architectural spatial composition. The points of contact of painting and architecture lie in the plane of color solutions. The role of the academic education, traditional and checked by the time professional school that hasn't lost its significance in the field of the newest visual communications is also highlighted in this article. The visualization tools of our time in various computer and digital analogues further emphasize the importance of traditional visual and plastic arts, which are a figurative concentration of ideas and meanings.